Corporate Culture and Employee Performance in Telecommunication Companies: A Case Study of Airtel Branch in Ntungamo District - Honest Nimusiima (Uganda Christian University, 2025)
The study was about corporate culture and employee performance in telecommunication companies; a case of Airtel branch in Ntungamo District. The objectives of this study were; to assess the effect of involvement on employee performance in selected telecommunication companies, to examine the effect of consistency on employee performance in selected telecommunication companies and to analyze the effect of adaptability on employee performance in the selected telecommunication companies. The study used a cross-sectional research design employing both qualitative and quantitative approaches. A sample size of 88 respondents fully responded to questions administered to them. The study tested the first hypothesis; “There is no significant effect between involvement and employee performance in telecommunication companies in Ntungamo District” and it was rejected. This is because there was a high positive relationship between involvement and employee performance whereby an improvement in organization’s involvement increases on the performance of employees. The study therefore concluded that involvement positively affects employee performance in telecommunication companies. The study tested the second hypothesis: “There is no significant relationship between consistency and performance of employees in selected telecommunication”, and it was rejected. This is because there was a positive significant positive relationship between consistency and employee performance. The study further found that adaptability and employee performance were found to have a significant relationship. Lastly, according to the results presented in chapter four, mission and employee performance were found to have a significant positive relationship. Thus, the hypothesis that stated that mission does not have a significant effect on employee performance is rejected. The study recommended that there is need to build and improve teamwork. Putting a team in place to connect with each other, not just on a work level, but also on a friendship level, is beneficial towards more effective teamwork in the future. Team-building exercises are an easy way to get the team on the same level, familiar with one another, and better at communicating in a variety of environments. Planning out-of-office retreats and exercises for the team is also a great way to encourage better teamwork.
Undergraduate Research